2016
DOI: 10.1007/s10096-016-2737-2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical monotherapy with meropenem or combination therapy: the microbiological point of view

Abstract: The increase in the number of clinical isolates of multiresistant Enterobacteriaceae and Pseudomonas aeruginosa raises problems in decision-making on empirical treatments for severe Gram-negative bacilli-associated infections. The aim of our study is to determine the resistance of meropenem in our setting and the co-resistance of a combination of this compound with two antibiotics from different families: amikacin and ciprofloxacin. Between 2009 and 2013, a total of 81,310 clinical isolates belonging to the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…(25.17%) ( Graph 2 ). This frequency was lower than the rates reported in Latin America in general (38.4%), Guatemala (75.8%), Peru (62.5%), and Ecuador (55.6%) in 2011 16 and in ICUs in India between 2015 and 2016 (56%), 15 and was more aligned with rates found in Spain in 2013 (24.52%) 19 and other countries such as Poland, Lithuania, Slovakia, Hungary, Croatia, Romania, Bulgaria, and Greece, where the frequency of carbapenem resistance ranges from 25% to 50%. 20 …”
Section: Discussioncontrasting
confidence: 56%
“…(25.17%) ( Graph 2 ). This frequency was lower than the rates reported in Latin America in general (38.4%), Guatemala (75.8%), Peru (62.5%), and Ecuador (55.6%) in 2011 16 and in ICUs in India between 2015 and 2016 (56%), 15 and was more aligned with rates found in Spain in 2013 (24.52%) 19 and other countries such as Poland, Lithuania, Slovakia, Hungary, Croatia, Romania, Bulgaria, and Greece, where the frequency of carbapenem resistance ranges from 25% to 50%. 20 …”
Section: Discussioncontrasting
confidence: 56%
“…Garcinuño P et al, in their study, showed a higher microbiological success rate with Amikacin and Meropenem. 18 Escherichia coli showed 100% sensitivity to Amikacin followed by Meropenem and Imipenem. A study done by Kidwai S et al showed Escherichia coli with highest sensitivity to Imipenem followed by Amikacin.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of amikacin therapy resulted in a more than threefold reduction in the risk of resistance. 27 Overuse of fl uoroquinolones in the treatment of P. aeruginosa infections increased bacterial resistance to fluoroquinolones in recent years. Resistance to fl uoroquinolones is mainly due to: (1) point mutations in the DNA gyrase (gyrA and gyrB) and topoisomerase IV (parC and parE) genes, (2) the presence of transferable plasmid-mediated quinolone resistance (PMQR), and (3) mutations in genes that regulate efflux expression and decreased expression of outer membrane porins.…”
Section: Discussionmentioning
confidence: 99%